2022
DOI: 10.3389/fphar.2022.894233
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Properties of Jasione montana Extracts and Their Main Secondary Metabolites

Abstract: The effects of different extracts obtained from Jasione montana L. (JM1–JM6) and their main metabolites on biological processes during wound healing were evaluated. The effect on wound closure in the scratch test was established, and collagen type I synthesis and anti-inflammatory effects were assessed by flow cytometry in a human dermal fibroblast model (PCS-201-012). Additionally, the antioxidant activity (DPPH and FRAP) and degree of inhibition of elastase participating in the proliferation processes of ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The eutectic-based extract (PG-50-TP) demonstrated a statistically significant superior inhibitory effect with an IC 50 value of 4.14 ± 0.02 µL of extract/mL. This confirms the results of a previous study which found that luteolin-rich J. montana extracts are excellent inhibitors of elastase [ 18 ].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The eutectic-based extract (PG-50-TP) demonstrated a statistically significant superior inhibitory effect with an IC 50 value of 4.14 ± 0.02 µL of extract/mL. This confirms the results of a previous study which found that luteolin-rich J. montana extracts are excellent inhibitors of elastase [ 18 ].…”
Section: Resultssupporting
confidence: 87%
“…High antiradical activity of OPT-TP is not surprising because phenolics, due to their chemical structures, may donate hydrogen to free radicals and thus strongly contribute to the antioxidant activity of the prepared extracts [ 41 ]. A previous study has shown that luteolin-rich J. montana extracts are potent radical scavengers [ 18 ]; however, it is difficult to compare the results of that study to those obtained in this work due to different measurement units. In the same work, performed on a smaller number of extracts, it was reported that the RSA correlates with luteolin content [ 18 ]; however, the results obtained in this study indicate that other phenolics present in the extracts also play an important part in the RSA of the extracts.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…These chemicals increase fibroblast viability, migration, and collagen formation, speeding wound healing. These chemicals' antioxidant characteristics limit ROS and oxidative stress, which aid wound healing (Barku, 2019;Juszczak et al, 2022). The study found that ethanol cardamom extracts better suppress harmful microorganisms like E. coli and S. aureus than methanol extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Migration assay At a density of 35,000 cells per well, fibroblasts were seeded and incubated until confluent. Using a 200 μl pipette tip as described byJuszczak et al[39], a scratch was made in each well. Before adding the medium conditioned with different concentrations of each plant extract (10 and 20 μg/ml), the media was withdrawn and the cells were rinsed * Significant at P < 0.05 over the negative control.…”
mentioning
confidence: 99%